2022
DOI: 10.1073/pnas.2114851119
|View full text |Cite
|
Sign up to set email alerts
|

D-mannose facilitates immunotherapy and radiotherapy of triple-negative breast cancer via degradation of PD-L1

Abstract: Breast cancer is the most frequent malignancy in women worldwide, and triple-negative breast cancer (TNBC) patients have the worst prognosis and highest risk of recurrence. The therapeutic strategies for TNBC are limited. It is urgent to develop new methods to enhance the efficacy of TNBC treatment. Previous studies demonstrated that D-mannose, a hexose, can enhance chemotherapy in cancer and suppress the immunopathology of autoimmune diseases. Here, we show that D-mannose can significantly facilitate TNBC tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…Given the rate of PD-L1 presence in TNBC cells, targeting this mechanism is thought to bear good potential in TNBC treatment [ 39 , 71 , 72 ]. Another animal study supported this finding, namely that interference with glycosylation of PD-L1 leads to its loss of function and in turn increases the efficacy of immunotherapy and radiotherapy in TNBC [ 73 ]. A combinatorial treatment with epidermal growth factor receptor (EGFR) inhibitor gefitinib and a saccharide analogue, 2-deoxy-D-glucose can enhance antitumor immunity in murine model of TNBC by deglycosylation of PD-L1 [ 74 ].…”
Section: The Impact Of Glycosylation Changes On Bc Treatment Outcome ...mentioning
confidence: 83%
“…Given the rate of PD-L1 presence in TNBC cells, targeting this mechanism is thought to bear good potential in TNBC treatment [ 39 , 71 , 72 ]. Another animal study supported this finding, namely that interference with glycosylation of PD-L1 leads to its loss of function and in turn increases the efficacy of immunotherapy and radiotherapy in TNBC [ 73 ]. A combinatorial treatment with epidermal growth factor receptor (EGFR) inhibitor gefitinib and a saccharide analogue, 2-deoxy-D-glucose can enhance antitumor immunity in murine model of TNBC by deglycosylation of PD-L1 [ 74 ].…”
Section: The Impact Of Glycosylation Changes On Bc Treatment Outcome ...mentioning
confidence: 83%
“…To test whether the PD‐L1 down‐regulation would affect PD‐1 binding, we incubated tumor cells with recombinant mouse PD‐1 (CD279) Fc protein. [ 19 ] Immunofluorescence showed that IR‐LND@Alb remarkably reduced PD‐1 binding to tumor cells (Figure 3G and Figure S25B, Supporting Information). Furthermore, we evaluated the efficacy of IR‐LND@Alb on T‐cell‐mediated tumor cell killing.…”
Section: Resultsmentioning
confidence: 99%
“…Given the homeostatic role and ubiquitous expression of MPI (Proudfoot et al, 1994), supraphysiological concentrations of mannose are required to trigger its anti-cancer activity in a wide variety of cancer cells (Gonzalez et al, 2018; Zhang et al, 2022). This limitation may hamper the possible clinical use of mannose in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%